غزوة بدر الموعد: السبب، التاريخ، والنتائج. (Al-Aasar, 2025)
This study examines the Expedition of Badr al-Mawʿid, highlighting its causes, historical context, and impact on the course of the Islamic mission. It begins by defining the expedition, explaining its name and geographical location, and then discusses the reasons for its occurrence. The study addresses the historical disagreement among early biographers regarding its date. Based on the most reliable narrations and the chronological sequence of events in the Prophetic biography, the author argues that the expedition took place in the fourth year after Hijrah, as a fulfillment of the appointment made by the polytheists after the Battle of Uḥud.The paper also analyzes Abū Sufyān’s attempt to deter the Muslims from marching out, the departure of the Muslim army under the leadership of the Prophet(PBUH) and the corresponding movement of the polytheists. It further explains how God thwarted the schemes of the disbelievers without actual combat. The study concludes by highlighting the expedition’s role in strengthening the Muslims’ morale, reinforcing their political standing, and affirming reliance upon divine promise rather than material strength